Conhecimento e percepção dos alunos do Curso de Arquivologia da UFPA sobre equipamentos de segurança nos ambientes arquivísticos - SOUZA, Dilcilene Maria Nascimento de (2021)
This work is result of a research that analyzed the perception of Federal University osPará Science Archival students regarding the use of security equipment in archival environments. The methodology that enabled the development of the research, according to the theme of this work consisted in a descriptive and exploratory approach, as well as bibliographic research and data collection. As a research instrument, a survey was applied to the students of the course of Science Archival of UFPA from classes of 2014, 2015 and 2016. From the answers obtained it was verified that the performance of their functions occurs, in a general way, in inadequate spaces and without the proper use of personal protective equipment - PPE.